2014
DOI: 10.1080/13548506.2014.993662
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between illness perceptions and cardiac misconceptions after Myocardial Infarction

Abstract: Research about cardiac misconceptions has focused on identifying the most common erroneous beliefs and understanding their impact on patients' outcomes. However, less is known about the underlying structure of cardiac misconceptions and how they relate to other belief dimensions. The aims of the present study were: (a) to characterize illness perceptions and cardiac misconceptions in a sample of Myocardial Infarction (MI) patients; (b) to analyse the structure of an experimental Portuguese version of the York … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A common cardiac misconception relates to the avoidance of stress. It is perceived to be a danger for patients with heart disease to get into arguments with people [ 6 ]. Other misconceptions include the view that people with heart problems must never get excited, and that having heart problems is a sign that the heart is worn out [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common cardiac misconception relates to the avoidance of stress. It is perceived to be a danger for patients with heart disease to get into arguments with people [ 6 ]. Other misconceptions include the view that people with heart problems must never get excited, and that having heart problems is a sign that the heart is worn out [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the maladaptive beliefs about heart disease held by nurses, nursing students, and patients with the disease, it was found that nursing students had fewer misconceptions than graduated nurses, while patients held significantly more misconceptions. As for patients with myocardial infarction, a common misconception is that they must avoid stress and excitement in their daily lives [ 6 ]. In a community sample of healthy adults, people who were older, male, or had not attained an academic degree were found to have more misconceptions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%